Defining and predicting progression in non-IPF interstitial lung disease. (November 2021) - Goos, Tinne; De Sadeleer, Laurens J.; Yserbyt, Jonas; De Langhe, Ellen; Dubbeldam, Adriana; Verbeken, Erik K.; Verleden, Geert M.; Vermant, Marie; Verschakelen, Johny; Vos, Robin; Weynand, Birgit; Verleden, Stijn E.; et al.
Abstract: Randomized placebo-controlled trials demonstrated the efficacy of antifibrotic treatment in non-IPF progressive fibrosing ILD (fILD). Currently, there is no consensus on how progression should be defined and clinical data of non-IPF fILD patients in a real-world setting are scarce. Non-IPF fILD patients presenting at the University Hospitals Leuven between 2012 and 2016 were included. Different definitions of progression according to the selection criteria of the INBUILD, RELIEF and the uILD study were retrospectively evaluated at every hospital visit. Univariate and multivariate analyses were performed to identify predictors of progression and mortality. The study cohort comprised 120 patients; 68.3%, 54.2% and 65.8% had progressive disease based on the INBUILD, RELIEF and uILD study, respectively. A large overlap of progressive fILD patients according to the different clinical trials was observed. Median transplant-free survival time of progressive fILD patients was 3.9, 3.9, 3.8 years and the median time-to-progression after diagnosis was 2.0, 3.1 and 2.3 years according to the INBUILD, RELIEF and uILD study, respectively. We identified several predictors of mortality, but only an underlying diagnosis of HP and uILD was independently associated with progression. Our data show a high prevalence of progressive fibrosis among non-IPF fILD patients and a discrepancy between predictors of mortality and progression. Mortality rate in fILD is high and the identification of progressive disease is only made late during the disease course. Moreover, future treatment decisions will be based upon disease behavior. Therefore, more predictors of progressive disease are needed to guide treatment decisions in the future. Highlights: Compared to RELIEF, progression based on INBUILD/uILD better predicts survival. Progression should be based on different parameters (symptoms, CT and PFT). High prevalence of progression and high mortality rate in patients with fibrosis >10%. A discrepancy between predictors of mortality and progression was observed. Predictors of progression are needed to guide treatment decisions in the future.